Suppression of piriform cortex activity in rat by corticotropin-releasing factor 1 and serotonin 2A/C receptors - Narla, Chakravarthi; Dunn, Henry A.; Ferguson, Stephen S.; Poulter, Michael O. (Frontiers in Cellular Neuroscience, 2015)
The piriform cortex (PC) is richly innervated by Corticotropin-releasing factor (CRF) and Serotonin (5-HT) containing axons arising from central amygdala and Raphe nucleus. CRFR1 and 5-HT2A/2CRs have been shown to interact in manner where CRFR activation subsequently potentiates the activity of 5-HT2A/2CRs. The purpose of this study was to determine how the activation of CRFR1 and/or 5-HT2Rs modulates PC activity at both the circuit and cellular level. Voltage sensitive dye imaging showed that CRF acting through CRFR1 dampened activation of the layer II of PC and interneurons of endopiriform nucleus. Application of the selective 5-HT2A/CR agonist 2,5-dimethoxy-4-iodoamphetamine (DOI) following CRFR1 activation potentiated this effect. Blocking the interaction between CRFR1 and 5-HT2R with a Tat-CRFR1-CT peptide abolished this potentiation. Application of forskolin did not mimic CRFR1 activity but instead blocked it, while a protein kinase A antagonist had no effect. However, activation and antagonism of protein kinase C (PKC) either mimicked or blocked CRF modulation respectively. DOI had no effect when applied alone indicating that the prior activation of CRFR1 receptors was critical for DOI to show significant effects similar to CRF. Patch clamp recordings showed that both CRF and DOI reduced the synaptic responsiveness of layer II pyramidal neurons. CRF had highly variable effects on interneurons within layer III, both increasing and decreasing their excitability, but DOI had no effect on the excitability of this group of neurons. These data show that CRF and serotonin, acting through both CRFR1 and 5-HT2A/CRs, reduce the activation of the PC. This modulation may be an important blunting mechanism of stressor behaviours mediated through the olfactory cortex.